Faktor Risiko dan Prevalensi Infeksi Toxocara vitulorum pada Sapi Potong di Kecamatan Kasiman, Kabupaten Bojonegoro - Aji Winarso; Fadjar Satrija; Yusuf Ridwan (Institut Pertanian Bogor, 2015)
This study were conducted to determine the presence of toxocariosis in beef cattle in Kasiman Subdistrict, the Regency of Bojonegoro kept under the Sekolah Peternakan Rakyat (SPR) programme. The experiment were done to identify several risk factors that may play certain roles on the degree of prevalence and infection intensity. A total of 263 head of local beef cattle with various ages were taken for faecal samples and 80 farmers were interviewed. Results of the experiment indicated the prevalence of toxocariosis was 5.32% (CI 95% = 2.61-8.04%) influenced by age and gender which showed an effect on the risk of infection. The prevalence tends to decline by age group (p <0.001): calves under 6 months of age (23.68%), and between 6-12 months of age (7.41%), 1-2 years old calves (2.04%) and the above 2 years adults (1.34%). The prevalence is higher in the males group (12.7%) compared to the females group (3.0%), (p=0.003). Logistic regression analysis concluded that age was the only affecting variable to the rate of infection with mathematical models for toxocariosis. Logit toxocariosis = -0.058 -1.098 age.